Pergeseran Merek Smartphone di Indonesia dalam Perspektif Postmodernisme - Fatria, Ashri Esy; Christantyawati, Nevrettia (Faculty of Communications Science, Dr. Soetomo University, 2018)
This research analyses the cause of smartphone brand shift in Indonesia during the period of five years in the period 2011 - 2016 which viewed from the perspective of postmodernism. This study proves that the shift of smartphone brand sales in Indonesia is influenced by the massive onslaught of advertising done by smartphone vendors (smartphone industry capitalist) to the consumer. So these advertisements obscure the reality (functional value) with the formation of symbols of communication that is not real so as to create a simulacra space that makes smartphone users stuck to the value of marks or symbols of smartphone products to simply meet the false social lifestyle. It certainly triggers the emergence of a strong consumerism culture and feared to cause poverty life of the people.